Can Corporate Responsibility Improve Business Financial Performance? A Research Insight - Kumaza, Alphonse; He, Yuanqiong (International Journal of Economics and Financial Issues, 2019)
Social responsibility engagement and business financial performance have received countless authorial observations. While many support the assertion that social responsibility imposes financial strains on the enterprise’s incomes, little proof exists to support the claim social responsibility engagement benefits the business. Thus, the study’s scrutiny of the proposition has produced an ample and concrete argument for the postulation, having recognised volatility and contentiousness of the corporate/responsibility dichotomy. Focused interviews generate data for analysis through an SPSS Regression technique for findings. The result indicates statistically significant the numerical tests and coefficients, which attest to corporate responsibility (CR) profiting businesses and, therefore, a strong proof that CR prospers enterprises operations. These social values (including social licence, legitimacy and good corporate public standing) when quantified, represent profits for the business. The evidence, therefore, provides a platform for local authorities and corporations’ dialogue on the social change agenda for social justice. The research establishes that quantification, in monetary value terms, of non-financial social indicators proves CR flourishes business activities. Thus, this measurement lack, for social licence, legitimacy and company’s good image, which constitute colossal corporate profits, and little scholarly work through this approach that social responsibility promotes business financial prosperity, is a significant departure from the traditional, general and unspecific treatment of societal non-financial assets. This is an unexplored, novel and pristine area and deserves a future academic examination. Keywords: Corporate Responsibility, Social Licence, Legitimacy, Business Financial Performance, Ghana JEL Classifications: L25, M14, O16 DOI: https://doi.org/10.32479/ijefi.7286